Measurement of Tailored agent-oriented design processes by resorting to flow graphs: A preliminary investigation - Garcia Ojeda, Juan C. (Revista Colombiana de Computación, 2010)
This work describes the OMaSE-based Flow Graph (OFG). OFG is a tool for assessing the advantages and disadvantages of tailored agent-oriented design process in assembling time.